Basal ganglia contributions during the learning of a visuomotor rotation: Effect of dopamine, deep brain stimulation and reinforcement. (16th July 2019) - Singh, Puneet; Lenka, Abhishek; Stezin, Albert; Jhunjhunwala, Ketan; Pal, Pramod Kumar; Ghosal, Ashitava; Murthy, Aditya
Abstract: It is commonly thought that visuomotor adaptation is mediated by the cerebellum while reinforcement learning is mediated by the basal ganglia. In contrast to this strict dichotomy, we demonstrate a role for the basal ganglia in visuomotor adaptation (error‐based motor learning) in patients with Parkinson's disease (PD) by comparing the degree of motor learning in the presence and absence of dopamine medication. We further show similar modulation of learning rates in the presence and absence of subthalamic deep brain stimulation. We also report that reinforcement is an essential component of visuomotor adaptation by demonstrating the lack of motor learning in patients with PD during the ON‐dopamine state relative to the OFF‐dopamine state in the absence of a reinforcement signal. Taken together, these results raise the possibility that the basal ganglia modulate the gain of visuomotor adaptation based on the reinforcement received at the end of the trial. Abstract : Basal ganglia modulate the gain of error‐based motor learning.